Penerapan Metode Storytelling untuk Meningkatkan Kemampuan Literasi pada Anak SD - Vivit Vitrianti; Desty Endrawati Subroto; Irma Raudotun Nissa; Anika Nuraeni; Seli Kristiany; Niswa Ziyan Ahlia (STIKes Ibnu Sina Ajibarang, 2025)
Literacy skills are a fundamental component of primary education, playing a crucial role in shaping students’ critical thinking, communication abilities, and character development. However, literacy levels among elementary school students in Indonesia remain low, as reflected in various national and international assessments. One contributing factor is the dominance of conventional teaching approaches that are less engaging and lack contextual relevance. This article aims to examine the effectiveness of the storytelling method as an innovative strategy to enhance literacy skills among primary school students. Through a literature review method, the article analyzes theories related to literacy, storytelling, and findings from previous studies. Storytelling has been proven to improve students’ listening, speaking, reading, and writing skills in an integrated manner. Furthermore, this method fosters emotional and intellectual engagement through enjoyable and meaningful learning experiences. Teachers play a vital role as facilitators in bringing stories to life and creating interactive learning environments. Therefore, storytelling is viewed as a strategic approach to strengthening children's literacy from an early age, while also addressing the limitations of conventional teaching methods commonly used in elementary schools.